Strategi Pemasaran Syariah Dalam Peningkatan Minat Beli Masyarakat Pada Bisnis Online Di Kecamatan Batulappa Kab. Pinrang - Rika; Mardia; Desy Arum Sunarta (CV. ALIM'SPUBLISHING, 2023)
Marketing strategy is a plan to increase influence over the market, both in the short and long term, based on market research, product strategy, price, promotion and distribution sites. Purchase intention is part of the behavioral component in consumption attitudes, the tendency of respondents to act before buying decisions are actually implemented. Meanwhile, repurchase intention is a purchase intention based on past purchasing experience. The purpose of this study is to determine the factors that influence sharia marketing strategies, determine sharia marketing strategies and to determine the impact of sharia marketing strategies in increasing people's buying interest in online business. This research is included in qualitative research, meaning that this research produces descriptive data in the form of written or oral words from the people and the observed behavior. The approach used is a descriptive qualitative approach, which means that the data collected is in the form of words, pictures, and not in the form of numbers. The results of the study show that the factors that influence sharia marketing strategy are competitors, technology, network, finance, goods and access. Then, the sharia marketing strategy for online business is product strategy, price strategy, place strategy and promotion. The impact of the sharia marketing strategy on online business is that it can increase sales and public buying interest in online sales.